But is it art? : an introduction to art theory - Freeland, Cynthia A. (Oxford ; New York : Oxford University Press, 2001)
"In today's art world many strange, even shocking, things qualify as art. In this book, Cynthia Freeland explains why innovation and controversy are valued in the arts, weaving together philosophy and art theory with many fascinating examples." "She discusses blood, beauty, culture, money, museums, sex, and politics, clarifying contemporary and historical accounts of the nature, function, and interpretation of the arts. Freeland also propels us into the future by surveying cutting-edge web sites, along with the latest research on the brain's role in perceiving art." "This clear, provocative book engages with the big debates surrounding our responses to art and will prove an invaluable introduction to anyone interested in thinking about art."--BOOK JACKET.
1 Blood and beauty 1 -- 2 Paradigms and purposes 30 -- 3 Cultural crossings 60 -- 4 Money, markets, museums 90 -- 5 Gender, genius, and Guerrilla Girls 122 -- 6 Cognition, creation, comprehension 148 -- 7 Digitizing and disseminating 177.
Includes bibliographical references (p. 210-221) and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Aesthetics; Art -- Philosophy; Art criticism; Art and society; Electronic books